Scottish clan identities in America: symbolic or real?. Issue 14 (13th November 2016) - Leith, Murray Stewart; Sim, Duncan
ABSTRACT: This paper explores Herbert Gans's notion of symbolic ethnicity and his recent assertions that it is effectively at an end and little more than a label. We use research into Scottish-American clan associations to question this assertion and we seek to demonstrate that symbolic ethnicity appears to be alive and well within such diaspora organizations. The paper reports on a series of interviews conducted in 2014 with office bearers and members of clan associations and we use our findings to argue, along with other writers such as Steinberg that, when considering hyphenated ethnicity, it is important not to underestimate the power of the hyphen.